Experimental evaluation of four protocols for assessing white-tailed deer browse intensity - Brendan R. Quirion; Bernd Blossey (Ecological Indicators, 2023)
Native and introduced deer populations have expanded on many continents and are now considered primary drivers of ecosystem degradation. Large herbivore management can be controversial, requiring appropriate tools to gauge impacts and guide management decisions. While many different protocols have been proposed to measure deer impacts to vegetation, few have been experimentally validated to assess whether they respond reliably to changes in deer browse intensity.Here we used a network of large (2 ha) long-term deer exclosures in New York State to assess utility and reliability of AVID (Assessing Vegetation Impacts of Deer), the Ten-Tallest, and Twig-Age protocols to capture changes in white-tailed deer (Odocoileus virginianus) browse intensity. We also assessed whether three herbaceous species: blue-stemmed goldenrod (Solidago caesia), white wood aster (Eurybia divaricata), and zigzag goldenrod (Solidago flexicaulis) could expand upon a red oak (Quercus rubra) Sentinel protocol. Finally, we evaluated whether these four protocols adhered to criteria defined for ecological indicator selection.AVID, Ten-Tallest, and Twig-Age protocols rely on existing vegetation to measure deer browse intensity, which limited their ability to adhere to basic sampling principles and be standardized across different forest types, especially in areas with little vegetation remaining in browse height. The Ten-Tallest protocol did not consistently detect differences in deer browse intensity, calling into question its scientific validity. The Sentinel protocol utilizes propagated and planted species, which standardizes impact assessments across sites and captures annual changes in deer browse intensity. Sentinel met nearly all criteria required to function as a reliable deer browse indicator. Validation and selection of additional sentinel species is necessary to build out a portfolio of regionally relevant species that can gauge deer browse intensity across vegetation and habitat types. Of the herbaceous species evaluated, S. caesia showed promise as a new sentinel species, but further evaluations are necessary. Evidence-based deer management will require scientifically rigorous and validated impact monitoring approaches and metrics. We caution against adopting protocols that have not been thoroughly vetted to avoid misguided deer management and policy.